Theory for the Job: Comparing Human Capital and Cultural Capital to Understand Graduates Employability - Xin Zhou (Studies in Social Science & Humanities, 2023)
The employability of graduates is an important factor in linking higher education institutions to the labour market. As higher education continues to expand, master’s degrees are gradually becoming more popular in the Chinese job market. This essay will focus on the inequality in employability between Chinese students who have obtained their master’s degrees in UK universities and those who have obtained their master’s degrees in local Chinese universities. Moreover, this essay analyses the causes of this inequality by applying cultural capital theory and human capital theory, including the specific definitions, key concepts and problem analyses of the two theories. Finally, the purpose of comparing and contrasting the two theories is to explain the educational inequity of different employability resulting from the same academic qualifications.